Exploring Social Enterprise Leadership Development Through Phenomenological Analysis - Ilac, Emerald Jay D (Archīum Ateneo, 2018)
Purpose The purpose of this paper is to construct a theorized leadership development model for social enterprises based on the experiences of its current leaders, highlighting what are inherently imperative processes and competencies future leaders should hold. Design/methodology/approach Using the epistemological lens of phenomenological analysis, it focuses on the developmental process elements for the social enterprise leader, between the individual and the environment, and the individual and the community. To formulate the model, multiple data collection methods were utilized. Findings Analyzing multiple experiences of different social enterprise leaders formed a suggested processual leadership development model, which discovers fundamental elements and skills necessary in their development. Research limitations/implications Findings provide a foundational basis in the continued development of social entrepreneurs as rooted in the unique experiences of current social enterprise leaders. A limitation worth noting is the contextual distinctiveness of experiences that may shape the leadership experience. Practical implications Findings provide a baseline theorized framework on the critical facets of leadership development for social enterprise. Pragmatically, this functions as a competency framework that can be transformed into concrete learning activities and training sessions. Originality/value This paper provides perspective into social enterprise leadership emergence. It underscores the processes involved in comprehending how these leaders evolve through interpreting context, understanding their value and creating awareness with and through others.